2021
DOI: 10.3390/cancers13040655
|View full text |Cite
|
Sign up to set email alerts
|

Syndecan-1 Overexpressing Mesothelioma Cells Inhibit Proliferation, Wound Healing, and Tube Formation of Endothelial Cells

Abstract: Malignant mesothelioma (MM) is an aggressive tumor of the serosal cavities. Angiogenesis is important for mesothelioma progression, but so far, anti-angiogenic agents have not improved patient survival. Our hypothesis is that better understanding of the regulation of angiogenesis in this tumor would largely improve the success of such a therapy. Syndecan-1 (SDC-1) is a transmembrane heparan sulfate proteoglycan that acts as a co-receptor in various cellular processes including angiogenesis. In MM, the expressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 44 publications
0
12
0
Order By: Relevance
“…SDC-1, a major component of glycocalyx, is an important signaling transmembrane protein molecule. SDC-1 has an extracellular glycosaminoglycan chain comprising HS, HA, and CS ( 13 , 15 ). First, SDC-1 protrudes from extracellular structural features and functions as a physical barrier, capturing signal molecules and directing them to receptors on the membrane ( 14 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…SDC-1, a major component of glycocalyx, is an important signaling transmembrane protein molecule. SDC-1 has an extracellular glycosaminoglycan chain comprising HS, HA, and CS ( 13 , 15 ). First, SDC-1 protrudes from extracellular structural features and functions as a physical barrier, capturing signal molecules and directing them to receptors on the membrane ( 14 ).…”
Section: Discussionmentioning
confidence: 99%
“…SDC-1 is a transmembrane heparin sulfate proteoglycan that carries various side chains, such as heparin sulfate (HS), chondroitin sulfate (CS), and hyaluronic acid (HA) ( 13 ). The SDC-1 core protein comprises extracellular, transmembrane, and intracellular regions ( 14 ).…”
Section: Introductionmentioning
confidence: 99%
“…During wound healing, β-toxin largely induced production of HGF, with subtle increases in PDGF-AA and endostatin, and a subtle decrease in MMP-8. Excess HGF in the serum is clinically used as an indicator of advanced atherosclerotic lesions, vascular lesions, and hypertension (63)(64)(65). Vascular lesions are accompanied by endothelial cell injury.…”
Section: Discussionmentioning
confidence: 99%
“…Vascular lesions are accompanied by endothelial cell injury. As such, it has been suggested that endothelial cells produce HGF to promote repair of damaged endothelial cells at these lesions (63)(64)(65). Hence, iHAECs might induce HGF as a protective mechanism in response to endothelial injury caused by β-toxin.…”
Section: Discussionmentioning
confidence: 99%
“…The chemokine receptor Cxcr4a is indispensable for this venous-to-arterial transformation to occur in the zebrafish, and the importance of CXCR4 appears conserved in mammals where CXCR4 expression is observed in the tip cells of developing mouse retinal arterial vessels [ 72 , 73 ]. In a recapitulation of development, both VEGF and BMP signalling have been shown to be highly upregulated in immune cells, fibroblasts and keratinocytes within mouse wounds, and these pathways appear to have a distinct role in modulating wound angiogenesis by differentially regulating endothelial cell tip vs. stalk cell identity in culture [ 74 , 75 , 76 , 77 , 78 , 79 , 80 ]. Additionally, live imaging of skin wound healing studies identified the migration of tissue resident endovascular progenitors (EVP) into the centre of wound granulation tissue and subsequent differentiation.…”
Section: Endothelial Cell Heterogeneity In Homeostasis and Repairmentioning
confidence: 99%